The small core of the German corporate board network - Mishael Milaković; Simone Alfarano; Thomas Lux (Kiel Institute for the World Economy (IfW), 2008)
We consider the current bipartite graph of German corporate boards and identify a small core of directors who are highly central in the entire network while being densely connected among themselves. To identify the core, we compare the actual number of board memberships to a random benchmark, focusing on deviations from the benchmark that span several orders of magnitude. It seems that the board appointment decisions of largely capitalized companies are the driving force behind the existence of a core in Germany's board and director network. Conditional on being a board member, it is very improbable to obtain a second membership, but multiple board membership becomes increasingly likely once this initial barrier is overcome. We also present a simple model that describes board appointment decisions as a trade-off between social capital and monitoring ability.
Keywords: D85; L20; M14; M51; 330; Board and director interlocks; network core; network formation; market capitalization; Vorstand; Führungskräfte; Soziales Netzwerk; Business Network; Mitgliedschaft; Kosten-Nutzen-Analyse; Theorie; Deutschland